Cognitive Behavioral Therapy: A Quasi-Experimental Study of Self Care Activity with Type 2 Diabetes Mellitus Patients - Jauhari, Jauhari (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Individuals diagnosed with diabetes mellitus require a multi-faceted approach to treatment. Key aspects of self-care for these patients include maintaining a proper diet, engaging in regular physical activity, adhering to prescribed medications, consistently monitoring blood glucose levels, caring for the legs, and managing smoking habits. Among the therapeutic interventions used in nursing, Cognitive Behavioral Therapy (CBT) is noteworthy. The purpose of this study was to examine the impact of CBT on self-care behaviors in patients with Type 2 diabetes mellitus. Utilizing a quasi-experimental design, this study implemented a pre and post-test control group methodology. A total of 32 participants were selected based on specific criteria and probability sampling methods were employed to determine the sample. Data was gathered using the Summary of Self-Care Diabetic Activity questionnaire. Findings from the study indicate that CBT significantly enhanced dietary compliance (p-value = 0.02), increased physical activity (p-value = 0.001), and improved independent blood glucose monitoring (p-value = 0.003). Additionally, CBT enhanced adherence to medication (p-value = 0.004), leg care (p-value = 0.004), and reduced smoking behaviors (p-value = 0.021). CBT effective in enhancing various self-care activities among diabetic patients by fostering changes in mindset and encouraging positive behavioral shifts